Development of Islam religious ideology is in Kazakhstan (Journal of Philosophy Culture and Political Science, 2019)
In the article the issues of modernization of Islamic culture, ideological functions of religion in modern society and strengthening of elucidative work in Kazakhstan are examined. Authors reveal the spiritual-religious bases of Islamic tradition, negative circumstances of religious ideology and offer the functions of safety. Gives short-story description to the faith of XXI ch. Keywords: religion, islam, ideology, culture, enlightenment.